Detection the level of YKL-40 biochemical marker and vitamin D level in sera of Iraqi Uterine cancer females' patients - Jasm, walaa; Farhan, amal; Abed, wasan (Iraqi National Journal of Nursing Specialties, 2013)
Objective: Detection the level of YKL-40 biochemical marker and vitamin D level in sera of Iraqi uterine cancerfemales' patients.Methodology: This study included 90 female volunteers, 30 of them were healthy volunteers who wereconsidered as a control group, while sixty serum samples were collected from women patients suffering fromuterine tumors (30 malignant and 30 fibroid benign tumors), benign cases were considered as a diseasecontrol group for malignant tumors. The average age of those females was 30-75 years, which matched thecontrol group. All the samples were collected from Azady hospital in Kirkuk and the gynecologic department atMedical City in Baghdad during October /2012 to May /2013. All the serum samples were undergonebiochemical estimation for the levels of YKL-40, and 25 (OH) vitamin D using ELISA technique, and BMI datawere collected.Results: Estimation of YKL-40 levels showed that there were 28 No. (93.33%) of EC patients had high level ofYKL-40, while 26 no. (86.67%) of fibroid (benign tumor) patients had low level, and 15(50.00 %) of healthycontrol had low. There was a significant difference found in YKL-40 level in EC patients when compared withthe fibroid (benign tumor) patients and healthy control (Pvalue= 0.0001), (Pvalue= 0.0001) respectively. Thehighest percent of women with EC and the women with fibroid (benign tumor) had deficiency of 25 (OH)vitamin D levels (66.67%). While the highest percent of healthy control had sufficiency of 25(OH) vitamin Dlevel (56.67%). statistically there was significant difference among study groups (p=0.0001). Were as nosignificant difference between EC patients and fibroid (benign tumor) patients (P-value =0.822).Recommendations: Comparing between the ykl-40 marker and other tumor marker diagnostic levels in thedetection of uterine tumors. For further studies, we recommended study the diagnostic levels of ykl-40marker and its correlation with other body tumors. It is recommended to do estimation of vitamin D levelswith more advanced method and correlation of its with disease.